Identification of three morphologically indistinguishable Epicauta species (Coleoptera, Meloidae, Epicautini) through DNA barcodes and morphological comparisons - Liu, Shao-Pan; Pan, Zhao; Ren, Guo-Dong (Zootaxa, 2016)
Three species that belong to the genus Epicauta (Coleopera: Meloidae), E. chinensis, E. dubia, and E. sibirica, appear morphologically indistinguishable. The present study aims to resolve the taxonomic status and the relationships among these three species. Identifying adult morphological characters among the three species were compared and illustrated and partial fragments of the mitochondrial gene (COI) for 77 samples, representing seven meloid species, were obtained and analyzed. Analyses of nucleotide composition, genetic distances and phylogenetics were performed. The results of the morphological studies and molecular analyses showed concordance, indicating that the three species are closely related and indistinguishable from one another. Consequently, two new synonyms are proposed: E. chinensis (Laporte, 1840) syn. n. = E. sibirica (Pallas, 1773) and E. dubia (Fabricius, 1781) syn. n. = E. sibirica (Pallas, 1773).